2019
DOI: 10.3389/fimmu.2019.02198
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Blockade of Spinal CXCL3/CXCR2 Signaling by NVP CXCR2 20, a Selective CXCR2 Antagonist, Reduces Neuropathic Pain Following Peripheral Nerve Injury

Abstract: Recently, the role of CXCR2 in nociception has been noted. Our studies provide new evidence that the intrathecal administration of its CINC ligands (Cytokine-Induced Neutrophil Chemoattractant; CXCL1-3) induces pain-like behavior in naïve mice, and the effect occurring shortly after administration is associated with the neural location of CXCR2, as confirmed by immunofluorescence. RT-qPCR analysis showed, for the first time, raised levels of spinal CXCR2 after chronic constriction injury (CCI) of the sciatic n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(63 citation statements)
references
References 111 publications
1
62
0
Order By: Relevance
“…Other cytokines from our top DE gene list, such as CXCL1, 2 or 3 (all ligands of the CXCR2 receptor), have also been shown to be pro-nociceptive [ 51 ]. Intrathecal administration of CXCL1, 2 or 3 produced hyperalgesia in mice [ 52 ]. These chemokines have also been implicated in neuropathic pain [ 52 54 ] and nociceptive sensitization after traumatic brain injury [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other cytokines from our top DE gene list, such as CXCL1, 2 or 3 (all ligands of the CXCR2 receptor), have also been shown to be pro-nociceptive [ 51 ]. Intrathecal administration of CXCL1, 2 or 3 produced hyperalgesia in mice [ 52 ]. These chemokines have also been implicated in neuropathic pain [ 52 54 ] and nociceptive sensitization after traumatic brain injury [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intrathecal administration of CXCL1, 2 or 3 produced hyperalgesia in mice [ 52 ]. These chemokines have also been implicated in neuropathic pain [ 52 54 ] and nociceptive sensitization after traumatic brain injury [ 55 , 56 ]. CXCL1 in the synovial fluid of osteoarthritis patients correlated with the severity of pain [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Liu found that CxCl3 was highly expressed in the cervical spinal cord of pruritus animal model, suggesting that CxCl3 may mediate pruritus [ 47 ]. In addition, Piotrowska proved that CXCL3 may mediate the process of neuropathic pain and hyperalgesia [ 48 ]. Consistent with these results, we found that PDYN and CXCL3 were differentially expressed in the DRG of PHN rats.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, CXCR2 antagonists have demonstrated an antinociceptive effect in the CCI model of NP [67]. Therefore, the femalespeci c upregulation of cxcr2 suggests that CXCR2 antagonists might be more e cacious for NP in females.…”
Section: Other Changes To the Immunological Responsementioning
confidence: 99%